Transforming engineering students into student engineers : improving learning outcomes and employability : final report. - Foley, Bernadette; Gill, Tiffany; Palmer, Edward; Senadji, Bouchra; Martinez-Marroquin, Elisa (Australia. Dept of Education, 2019)
In the past 10 years, there has been an increasing need and emphasis on ensuring that curricula prepares graduates for successful careers. The present project builds on the Australian Government’s Office for Learning and Teaching seed project (SD13-2878) entitled ‘Promoting student engagement and continual improvement: integrating professional quality management practices into engineering curricula’. The seed project conceptualised the Management System for Engineering Education (MaSEE) as a framework under which engineering students would be provided with a suite of resources that would enable them to approach their studies as student engineers, rather than engineering students, and aid them in their transition to the profession. The approach used by professional engineers is informed by management system frameworks that set out consistent protocols and processes for use. The ability to appreciate and work in accordance with these protocols and processes provides transferable skills that are directly related to the employability of graduates and engineers. The MaSEE concept is predicated on similarities between industry management system processes, effective learning and teaching strategies and the development of employment capabilities. For example, adapted industry design verification protocols can be embedded into learning activities as a form of peer-generated cyclical feedback. This provides student engineers with the opportunity to use an adapted industry process and enables them to benefit from peer feedback in their learning. The project team engaged with industry members and educators to review the MaSEE concept and develop a modular and flexible suite of processes that could be used by individual educators or scaffolded throughout a program. Six processes – design verification, design review, project minutes, document control, risk assessment and project planning were initially proposed and were later confirmed as appropriate processes by industry members through this project. [Executive summary, ed]